2012
DOI: 10.1093/infdis/jir799
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacovigilance of Malaria Intermittent Preventive Treatment in Infants Coupled With Routine Immunizations in 6 African Countries

Abstract: Simultaneous administration of SP-IPTi and immunizations is a safe strategy for implementation with a low risk of serious AEs to infants. Strategies toward strengthening spontaneous reporting in Africa should include not only the provider but also beneficiaries or their caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…A study in Malawi showed that the incidence of severe skin reactions in children from use of SP for malaria treatment is very low, only 2 events were recorded in over 300,000 treatments [ 12 ]. A study of the safety of SP used for IPTi, through passive follow-up of 217,000 SP treatments and active follow up of 24,000 children treated with SP, found no serious adverse reactions [ 13 ] and an Institute of Medicine review [ 14 ] looked specifically at the safety of SP for IPTi and concluded that it was well tolerated. Our surveillance did not detect any cases of severe cutaneous reactions associated with SMC drugs.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Malawi showed that the incidence of severe skin reactions in children from use of SP for malaria treatment is very low, only 2 events were recorded in over 300,000 treatments [ 12 ]. A study of the safety of SP used for IPTi, through passive follow-up of 217,000 SP treatments and active follow up of 24,000 children treated with SP, found no serious adverse reactions [ 13 ] and an Institute of Medicine review [ 14 ] looked specifically at the safety of SP for IPTi and concluded that it was well tolerated. Our surveillance did not detect any cases of severe cutaneous reactions associated with SMC drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The same estimates may reasonably apply to the alternative combination amodiaquine plus sulfadoxine-pyrimethamine, as this was found as effective as ACT in the study area [42]. As far as safety is concerned, amodiaquine is the partner drug of one of the most widely used ACTs, and the combination, as well as sulfadoxine-pyrimethamine alone, have been tested in several randomized controlled trials [42]–[45], while sulfadoxine-pyrimethamine has been extensively used as intermittent preventive treatment both in pregnancy and in infants, showing an excellent safety profile [46], [47].…”
Section: Methodsmentioning
confidence: 99%
“…Rather, it was thought key to emphasize the verbal explanation of adverse events by health professionals to caregivers, initiating a more conversational approach that would enable concerns to be addressed and to encourage caregivers to attend the clinic should adverse events occur. The balance between provision of sufficient information on potential adverse events and raising unnecessary concerns has not been well examined, and this is an area which could benefit from further qualitative study, particularly in the context of strengthening pharmacovigilance systems [ 13 , 40 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sulfadoxine-pyrimethamine (SP) has been widely used for chemoprevention in Africa, including for PMC, and studies have demonstrated its efficacy safety and tolerability [ 5 11 ]. Furthermore, pharmacovigilance studies have confirmed the safety of simultaneous administration of SP and vaccines [ 12 , 13 ], making the Expanded Programme on Immunisation (EPI) a key channel for PMC delivery. PMC has been shown to reduce the incidence of clinical malaria by around 30%, as well as the incidence of anaemia, parasitaemia, and all cause hospital admissions in children aged 12 to 24 months [ 6 11 ].…”
Section: Introductionmentioning
confidence: 99%